2018
DOI: 10.1186/s13046-018-0703-9
|View full text |Cite|
|
Sign up to set email alerts
|

Novel smac mimetic APG-1387 elicits ovarian cancer cell killing through TNF-alpha, Ripoptosome and autophagy mediated cell death pathway

Abstract: BackgroundOvarian cancer is a deadly disease. Inhibitors of apoptosis proteins (IAPs) are key regulators of apoptosis and are frequently dysregulated in ovarian cancer. Overexpression of IAPs proteins has been correlated with tumorigenesis, treatment resistance and poor prognosis. Reinstalling functional cell death machinery by pharmacological inhibition of IAPs proteins may represent an attractive therapeutic strategy for treatment of ovarian cancer.MethodsCCK-8 and colony formation assay was performed to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…In the present study, the bivalent SMAC mimetic APG-1387 was able to induce almost complete reduction of cIAP1 and cIAP2, and suppressed XIAP to some extent in HCC cell line HepG2 and HCCLM3. However, unlike the significant anti-tumor effects of APG-1387 on ovarian cancer ( Li et al, 2018 ), nasopharyngeal carcinoma ( Li et al, 2016 ) and PLC/PRF/5 cells ( Pan et al, 2018 ), APG-1387 treatment alone, only showed limited inhibitory effects on HCC cell lines HepG2, HCCLM3 and Huh7, suggesting that HCC is more resistant to the SMAC mimetic than ovarian cancer or nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the bivalent SMAC mimetic APG-1387 was able to induce almost complete reduction of cIAP1 and cIAP2, and suppressed XIAP to some extent in HCC cell line HepG2 and HCCLM3. However, unlike the significant anti-tumor effects of APG-1387 on ovarian cancer ( Li et al, 2018 ), nasopharyngeal carcinoma ( Li et al, 2016 ) and PLC/PRF/5 cells ( Pan et al, 2018 ), APG-1387 treatment alone, only showed limited inhibitory effects on HCC cell lines HepG2, HCCLM3 and Huh7, suggesting that HCC is more resistant to the SMAC mimetic than ovarian cancer or nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several SMAC mimetics have been designed and are undergoing evaluation in early clinical trials as potential cancer therapeutic agents ( Fulda and Vucic, 2012 ; Fulda, 2015a ). APG-1387 is a novel bivalent SMAC mimetic that has been shown to have significant antitumor activities in ovarian cancer ( Li et al, 2018 ), nasopharyngeal carcinoma ( Li et al, 2016 ) and HBV-positive HCC cell line PLC/PRF/5 ( Pan et al, 2018 ), but has yet to be evaluated in other HCC cell types that resistant to its monotherapy. In this study, we examined the expression of IAPs in human liver tumor tissues and investigated the combinational anti-tumor potential of APG-1387 with cytokines or immune cells in HCC cell lines that resistant to APG-1387 monotherapy, and in a mouse xenograft model of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that, in apoptosis-resistant leukemia cells, SMs can potentiate TNF-induced necroptosis by enhancing the formation of the necrosome complex [84,115]. Subsequently, SM treatment induced massive cell death and led to regression of tumors in solid tumors [116,117]. These findings indicated that SMs can combine with death receptors to trigger apoptotic cell death.…”
Section: Combined With Death-inducing Ligandsmentioning
confidence: 95%
“…APG-1387 (Ascentage Pharma) has shown anti-cancer effects as a single agent in vitro and in vivo in nasopharyngeal carcinoma cells and in ovarian cancer cells [100][101][102]. APG-1387 is currently in dose-escalation Phase I/II clinical trials to determine safety, tolerability, pharmacokinetics and anti-cancer activity in patients with advanced solid tumors or hematological malignancies (Table 2) (NCT03386526, ACTRN12614000268640 and CTR20150161) [103,104].…”
Section: Other Smac-mimetic Drugsmentioning
confidence: 99%